South elevation of the Shiva temple - Temples of India Project Team (Jio Institute, 2024)
South Elevation of the Shiva temple containing a mandapa having lateral transepts as in many temples within Arthuna. There are restorations done to the main shekhari shikhara of the temple. The shikhara above the mandapa can be used as an analogy to understand the mandapa shikharas of other temples in Arthuna. The niches at the base of the shekhari shikhara contain images of Digambar Shiva, Shiva flanked by Vishnu and Brahma and Lakulisha, on the south, west and north elevations.